Spontanuous Demand For Meningococcal B Vaccination: Effects On Appropriateness And Timing. Issue 8 (3rd August 2018) - Giuliani, A. R; Mattei, A; Appetiti, A; Pompei, D; Di Donna, F; Fiasca, F; Fabiani, L
ABSTRACT: When the meningococcus B vaccine was introduced into Italy in 2017, it was recommended for newborns based on national epidemiological data indicating that they were at greater risk. However, the vaccination service of the local health authority of L'Aquila had already been receiving spontaneous parental requests to provide vaccination for children in lower-risk age groups from the beginning of 2016. We therefore decided to use a self-administered questionnaire in order to investigate the parents' socio-demographic data; their children's history of other recommended vaccinations (against measles, mumps and rubella, varicella, meningococcus C and, for females, human papilloma virus); the information sources concerning meningococcal vaccination; and the timing of its administration. The questionnaire was completed by 565 parents, and the results showed that the requests mainly came from the parents of children aged 5–11 years. The children whose mothers had received a high school education and were >35 years old were more likely to have received the first dose after the age of one year and to have perceived pain at the inoculation site, and less likely to have experienced mild general reactions. The requests were mainly trigged by the recommendations of healthcare professionals, and the overloading of the vaccination service led to delays in the administration of the doses after the first. The delays (reported by 74.07% of the parents) were mainly due to organisational problems in the service itself, which led 61.52% of the doses being more appropriately administered by staff working as private physicians inside public health facilities, albeit at extra cost. These findings indicate that organisational factors and excessive demand had a considerable impact on both the efficacy of the immunisation and its appropriateness.